Kinerja Angkutan Umum Penumpang Dalam Kota Makale, Tana Toraja - Monalisa Bumbungan; Rais Rachman; Frengki Demmangngaya Timbang (Paulus Civil Engineering Journal, 2023)
The research project attempts to assess the degree of service offered by public transportation in Makale City, Tana Toraja, as well as the load factor of passenger public transportation. Through the utilization of the Ms Excel software and the implementation of a weighting technique to assess the effectiveness of public transportation, the subsequent discoveries were derived from the data analysis: The average load factor of public transportation passengers in Makale City, Tana Toraja Regency is below 70.0%, with an average of 27.0% falling into the good category. The analysis of data using the weighting method revealed that the Makale City route in Tana Toraja Regency has an average travel time of 4 minutes per kilometer, which is considered good. The Average Headway, at 3.5 minutes, also falls into the good category. The Average Travel Speed is 15 km/h, classified as good. The Service Time, amounting to 14 hours, falls into the medium category. Additionally, the average frequency is 22 units, categorized as good. The number of operating vehicles is 145 units, also considered good. Finally, the average waiting time is 1.5 minutes, indicating good performance. In conclusion, the overall transportation performance is categorized as good.